COMPLIANCE TO MEDICATION IN HYPERTENSIVE PATIENTS OF CHRONIC DISEASE MANAGEMENT CONSULTING PHARMACIST AT PUBLIC HEALTH CENTER OF SEMARANG CITY - Meki Pranata; Rino Arianti Marswita; Farrah Bintang Sabiti (Jurnal Farmasi Sains dan Praktis, 2020)
One of the pharmaceutical services that can be done by pharmacists is counseling. Counseling lead to increase the obedience to taking medication in reduce hypertension. The objective of this research is to evaluate the obedience to drug therapy of hypertensive patient which already get counseling by pharmacists in Public Health Center in Semarang. This research was carried out by cross sectional design. The research was conducted towards 40 patients who were willing to take part in the research by filling out inform consent. “Pill count” method was used to evaluate the obedience level by counting the remaining drug for 1 month starting from the beginning until the end of July 2019. These results will be analyzed by chi-square test to determine the relationship between the characteristics and the obedience level. Wilcoxon test was done to determine the differences in groups before and after given counseling. The results showed that there was a significant decrease in systolic and diastolik pressure (p = 0,000). Chi-square test results showed that counseling given by pharmacists had no significance effect related to the obedience to drug therapy of hypertensive prolanis patient with a statistic of p> 0.05.